Impact of cyclodextrin treatment on composition and sensory properties of lingonberry (Vaccinium vitis-idaea) juice - Niina Kelanne; Oskar Laaksonen; Tanja Seppälä; Wei Yang; Kristiina Tuukkanen; Jussi Loponen; Baoru Yang (Elsevier, 2022)
Lingonberry (Vaccinium vitis-idaea L.) juice was treated with 10 g/L cyclodextrins (CD) or gelatin as potential means to improve the stability of bioactive compounds and to modify the sensory properties. Before and after the treatment acids, sugars, and phenolic compounds (anthocyanins, flavonols, phenolic acids, proanthocyanidins) of the juices were analyzed with chromatographic and mass spectrometric methods. Forty-six phenolic compounds were identified or tentatively identified, of which twenty-four were A-type or B-type proanthocyanidins with degree of polymerization of 1 to 9. Juices treated with β-CD had the highest contents of phenolic compounds (phenolic acids 17.9 mg/100 mL, flavonols 47.5 mg/100 mL, anthocyanins 21.0 mg/100 mL, and proanthocyanidins 114.2 mg/mL), whereas gelatin treatment resulted in significantly lowered content of the compounds (phenolic avids 16.3 mg/100 mL, flavonols 43.50 mg/100 mL, anthocyanins 19.7 mg/100 mL, and proanthocyanidins 81.7 mg/mL). Taste and astringency attributes of the juices were investigated with untrained panelists (n=40). The lingonberry juices were perceived as notably sour, bitter and astringent. CD or gelatin treatments alone had less effect on the astringency of the juice in comparison to their use in combination. The results suggest that, CDs may be utilized as protectants of the phenolic compounds, especially anthocyanins, in lingonberry juices.